2016
DOI: 10.1002/jcsm.12163
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia predicts readmission and mortality in elderly patients in acute care wards: a prospective study

Abstract: BackgroundThe aim of this study is to assess the prevalence of sarcopenia and investigate the associations between sarcopenia and long‐term mortality and readmission in a population of elderly inpatients in acute care wards.MethodsWe conducted a prospective observational study in the acute care wards of a teaching hospital in western China. The muscle mass was estimated according to a previously validated anthropometric equation. Handgrip strength was measured with a handheld dynamometer, and physical performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
171
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(186 citation statements)
references
References 33 publications
12
171
1
2
Order By: Relevance
“…A recent study demonstrated that sarcopenia evaluated by a combination of anthropometric measures, gait speed, and handgrip strength, is valuable for predicting hospital readmission and long-term mortality in elderly patients in acute care wards [4]. This study confirmed these findings in an elderly inpatient population with CVD.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A recent study demonstrated that sarcopenia evaluated by a combination of anthropometric measures, gait speed, and handgrip strength, is valuable for predicting hospital readmission and long-term mortality in elderly patients in acute care wards [4]. This study confirmed these findings in an elderly inpatient population with CVD.…”
Section: Discussionsupporting
confidence: 79%
“…These results were confirmed in a recent systematic review and meta-analysis [41]; they examined the prognostic influence of sarcopenia defined by the EWGSOP criteria in older people, in a meta-analysis including 12 cohort studies, and found a higher mortality rate among sarcopenic subjects (pooled odds ratio = 3.60; 95% CI = 2.96 -4.37) [41]. Although the prognostic value of sarcopenia is controversial in general Asian populations [10,42], it is robust in hospitalized elderly patients [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 The effects of sarcopenia are not only restricted to the loss of skeletal muscle mass but are also associated with muscle dysfunction and impaired physical performance, which may be exacerbated by chronic diseases. 39 Therefore, patients are in dire needs for a specialized sarcopenia therapy. 39 Therefore, patients are in dire needs for a specialized sarcopenia therapy.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 99%